Rancang Bangun Sistem Pengelolaan Ruangan Berbasis Website - Ayu Latifah; Asep Deddy Supriatna; Imam Saputra (Jurnal Sistem Cerdas, 2022)
Abstract— Currently the benefits of using information technology affect the human environment, one of which is organizational performance on campus, which has rooms for lectures, student activities and other parties. One of the problems faced in the university environment is the management of the room, when the room is being used or will be borrowed. Room management, which is still done manually, makes it difficult to borrow rooms and get information on the schedule for the use of the room used. Therefore we need a room management system that can make it easier to borrow according to the room you want to use, can schedule rooms outside the use of lectures according to what has been scheduled in the university environment. The purpose of this research is to create a website-based room management system on campus. In order to make it easier for related parties to help an organization so that they can provide information, management, and business processes that run in an organization. The methodology used in designing this software is the Rational Unified Process (RUP) with inception, elaboration, construction, and transition stages. The modeling used in software design is the Unified Modeling Language (UML). The results of the research that has been carried out is that a website-based room management system can borrow rooms, provide information regarding rooms whether they are being used or not, schedule room use outside of the use of lectures that have been scheduled in the campus environment.Keywords—Space, Information Systems, Rational Unified Process